2008
DOI: 10.1007/s00198-008-0721-0
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk increases after diagnosis of breast or other cancers in postmenopausal women: results from the Women’s Health Initiative

Abstract: Summary-Risk for falls and fractures increases after breast cancer or other cancer diagnosis in postmenopausal women. Factors other than falls may be the major causes for the increased fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 25 publications
(19 reference statements)
2
75
0
1
Order By: Relevance
“…This study confirms that hip fracture patients have substantial excess costs during the first two years following a fracture, and suggests that patients with fractures of the femur or pelvis have comparable excess costs, which is consistent with the literature pertaining to one year costs [8][9][10][11][12][13]. Moreover, while patients with fractures of the lower leg, forearm, and other NVNH sites have lower costs on a per person basis, they made up a much larger proportion of this study's sample.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study confirms that hip fracture patients have substantial excess costs during the first two years following a fracture, and suggests that patients with fractures of the femur or pelvis have comparable excess costs, which is consistent with the literature pertaining to one year costs [8][9][10][11][12][13]. Moreover, while patients with fractures of the lower leg, forearm, and other NVNH sites have lower costs on a per person basis, they made up a much larger proportion of this study's sample.…”
Section: Discussionsupporting
confidence: 90%
“…First, any patient with a medical claim with an E-code for severe trauma within 30 days of the index fracture was excluded from the sample, as these fractures may not have been related to osteoporosis [7,16,17]. In addition, patients with other conditions found to elevate fracture risk were excluded including those with diagnoses of metastatic cancer, bone cancer, multiple myeloma, and Paget's disease of bone, those who underwent surgical castration, and those using specific cancer drugs [18][19][20]. In an effort to further focus specifically on NV fracture patients, those with fractures of the vertebrae, trunk, face, skull, finger, toe, and unspecified sites were also excluded.…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking these factors into account, each woman will have a peak bone mass and a unique set of risk factors for bone loss that determines whether she will experience a non-traumatic fracture or osteoporosis. In postmenopausal women with breast cancer, the relative risks of osteoporotic fractures are higher than women without history of breast cancer [4].Estrogens play a central role in maintaining bone mass [5], and estrogen deficiency whether through natural menopause or as result of treatments for breast cancer such as oophorectomy, gonadotropin-releasing hormone (GnRH) agonist, chemotherapy-induced ovarian failure and aromatase inhibitors, and are associated with bone loss [6][7][8][9]. In order to explore the relationship between estrogens and bone, it useful to review briefly how normal bone maintains its' strength and structural integrity and what happens when estrogen deficiency occurs.…”
mentioning
confidence: 97%
“…Also, weakening in muscular strength may result in increased incidence of falls. A recent research has shown that BC survivors may have 15% increased risk of falls and 55% increased risk of hip fracture, compared to postmenopausal women without cancer (23). The sequelae of fractures lead to many adverse events such as major surgery, increased morbidity and mortality, increased cost of disease management and reduced QoL (24).…”
Section: -Diagnostic Densitometric T-score Values (Femoral Neck and Lmentioning
confidence: 99%